2014
DOI: 10.1007/s12034-014-0703-0
|View full text |Cite
|
Sign up to set email alerts
|

Processing, structure and flexural strength of CNT and carbon fibre reinforced, epoxy-matrix hybrid composite

Abstract: Advanced materials such as continuous fibre-reinforced polymer matrix composites offer significant enhancements in variety of properties, as compared to their bulk, monolithic counterparts. These properties include primarily the tensile stress, flexural stress and fracture parameters. However, till date, there are hardly any scientific studies reported on carbon fibre (C f) and carbon nanotube (CNT) reinforced hybrid epoxy matrix composites (unidirectional). The present work is an attempt to bring out the flex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…Ayatollahi et al (2011) have performed experiments on nanocomposites and have reported that by adding more MWNTs the viscosity of the mixture increases which makes the degassing of mixture more difficult. The synthesis route adopted in the present study was via a conventional hand layup technique as outlined elaborately by Chandra Shekar et al (2013). The densification and curing process is carried in a muffle furnace in three heat treatment cycles.…”
Section: Methodsmentioning
confidence: 99%
“…Ayatollahi et al (2011) have performed experiments on nanocomposites and have reported that by adding more MWNTs the viscosity of the mixture increases which makes the degassing of mixture more difficult. The synthesis route adopted in the present study was via a conventional hand layup technique as outlined elaborately by Chandra Shekar et al (2013). The densification and curing process is carried in a muffle furnace in three heat treatment cycles.…”
Section: Methodsmentioning
confidence: 99%
“…High strength values with high strength to weight ratio are obtained when compared to other competing polymer matrix composites. 12 Tensile strength and Flexural strength were increased in glass and flax fibre reinforced composites having MWCNT content of 1 wt.% upto28.26%. Compressive strength was decreased initially and then rapidly increased while increasing the MWCNT of 1 wt.%.…”
Section: Introductionmentioning
confidence: 95%
“…High strength values with high strength to weight ratio are obtained when compared to other competing polymer matrix composites. 12…”
Section: Introductionmentioning
confidence: 99%
“…These materials are used in aerospace, transportation, wind turbine blades, electromagnetic interference shielding, and expensive sporting goods, etc. [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. It is very important to understand whether CNT is attracted more by carbon fiber or epoxy resin in order to control the CNT dispersion.…”
Section: Introductionmentioning
confidence: 99%